2019
DOI: 10.1021/acs.analchem.9b05357
|View full text |Cite
|
Sign up to set email alerts
|

Cell Separations and Sorting

Abstract: The development of new methods and technologies for cell separation, sorting, selection, isolation, or enrichment (many times the aforementioned terms are used interchangeably) are becoming more imperative due in part to the wealth of research aimed at addressing issues for the analysis of liquid biopsy targets, such as rare cells, to realize the concept of "precision medicine". Precision medicine is defined as "treatments targeted to the needs of individual patients on the basis of genetic, biomarker, phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 243 publications
0
37
0
Order By: Relevance
“…In addition, size sorting techniques for GVs using microfluidic devices have recently been proposed following cell sorting microfluidic technology [ 67 ]. Kazayama et al reported that deterministic lateral displacement (DLD) is a promising mechanism for GV size sorting ( Figure 3 a).…”
Section: Manipulation Methods Of Gvsmentioning
confidence: 99%
“…In addition, size sorting techniques for GVs using microfluidic devices have recently been proposed following cell sorting microfluidic technology [ 67 ]. Kazayama et al reported that deterministic lateral displacement (DLD) is a promising mechanism for GV size sorting ( Figure 3 a).…”
Section: Manipulation Methods Of Gvsmentioning
confidence: 99%
“…With the advent of microfabrication, various novel microfluidic sorters have been developed to achieve the separation of different cells according to their biochemical and physical properties. 9–13 To meet the demands for rare cell separation, continuous efforts have been made to improve the processing throughput and separation precision. Researchers have successfully employed microfluidics to separate rare circulating tumor cells, 14–16 CTC clusters, 17 MTCs, 18 and fetal nucleated red blood cells 19 from clinical specimens with complex cell populations.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various separation techniques, magnetic separation is one of the most effective methods for the high throughput and low-cost isolation of target analytes. [13][14][15][16][17][18][19][20][21] Effective magnetic separation makes it possible to isolate circulating tumor cells in the blood for further analysis, which is crucial in cancer diagnosis and the development of personalized treatments. [22][23][24][25][26] Bacteria at very low concentrations can also be puried and concentrated effectively through magnetic separation to monitor food poisoning and infectious disease.…”
Section: Introductionmentioning
confidence: 99%